The investigation of the coupled vibration in a flexible-disk blades system considering the influence of shaft bending vibration. (October 2018) - She, Houxin; Li, Chaofeng; Tang, Qiansheng; Wen, Bangchun
Graphical abstract: Highlights: We establish the continuum model of the flexible shaft-disk-blades coupling system. As shaft goes further flexible, the shaft bending-disk bending-blade bending (SDB) mode occurs, increasing the types of coupling modes. With the decrease of disk's flexibility, BB modes bifurcate into BB and DB modes, TB and SB modes shift to TDB and SDB modes, respectively. The influence of rotational speed on mode frequencies indicates that shaft and disk flexibility can influence the critical rotational speeds greatly. Abstract: The continuum model of flexible shaft-disk-blades coupling system is established to investigate the coupling vibration among shaft-bending, shaft-torsion, disk-transverse and blade-bending. The influence of shaft bending rigidity, disk transverse rigidity and rotational speed on natural frequencies and mode shapes are particularly researched. The present paper discovers that when shaft bending is negligible, there are three types of coupling modes, shaft torsion-disk transverse-blade bending (TDB), disk transverse-blade bending (DB) and blade bending-blade bending (BB). As shaft goes further flexible, the shaft bending-disk bending-blade bending (SDB) mode occurs. What's more important is that shaft bending only couples with disk's 1-nodal diameter mode. Then the influence of disk transverse on coupling vibration is studied. With the decrease of disk's transverse rigidity, the repeated BB modes bifurcate into BB and DB modes, TB (shaft torsion-blade bending) and SB (shaft bending-blade bending) modes shift to TDB and SDB modes, respectively. Besides, disk's n-nodal (n ≥ 2) diameter modes always couples with blade bending when β ≠ 0°. At last, the effect of rotational speed on the frequencies is investigated, concluding that shaft flexibility and disk flexibility can significantly affect the critical speeds of the system.